Phylogeography of the freshwater red alga Sirodotia (Batrachospermales, Rhodophyta) in Brazil - Paiano, Monica Orlandi [UNESP]; Necchi Júnior, Orlando [UNESP] (Wiley, 2013)
Considering the lack of knowledge on genetic variation on members of the freshwater red algal of the order Batrachospermales in tropical regions, phylogeographic patterns in Sirodotia populations were investigate dusing two mitochondrial regions: the cox2-3 spacer and partial cox1 gene (barcode). Individuals identified as Sirodotia delicatula were analyzed from 14 stream segments across its distribution in Brazil. Phylogenetic analyses based on the ribulose-1,5-bisphosphate carboxylase/oxygenase large sub-unit gene showed three clades, one representing S. delicatula, from alllocations in southeastern Brazil and other regions from Brazil. The remaining samples formed two clades, which were highly divergent and distantly positioned from those of S. delicatula: 2.5–2.7% and 3.4–3.7%. This level of variation would warrant the species split of these taxa from mid-western Brazil. A total of eight cox2-3 spacer and nine cox1 haplotypes were observed among the 122 individuals studied. One location had two cox2-3 haplotypes and three locations had two cox1 haplotypes; all others had a single dominant haplotype each. The existence of high intraspecific genetic variation among individuals of distinct locations (several haplotypes), but little variation within a location seems to be a pattern for the Batrachospermales. Haplotype networks showed low variation among the haplotypes from southeastern Brazil (10 locations with divergence of 0.3–1.1% for cox2-3, 0.1–0.3% for cox1) and high variation among the haplotypes from the mid-west region (four locations, 4.0–9.3% for cox2-3, 6.2–8.4% for cox1). Thus, the present data clearly suggest the existence of cryptic species in Sirodotia in Brazil.
Keywords: Batrachospermales; cox1; cox2-3 spacer; cryptic species; phylogeography; rbcL; Rhodophyta; Sirodotia